Produção de texto escrito: como os alunos respondem às propostas da escola - Valquiria Rodrigues Silva Santos (2019)
This paperwork aims at analyzing the text production conditions of 5th grade students of elementary school from a public institution of the State of Minas Gerais. In order to endeavour the research, we assumed the conception of a language on its discursive and interactional aspect, relied on Bakhtin ([1929] 2002 and [1979] 1997); Brait (2016 and 2017); Costa Val (2000, 2007, 2008 e 2009); Marcuschi (2005 and 2008), among others. The qualitative approach was contemplated to understand the writing process in classroom (Alves-Mazzotti e Gewandsznajder, 2002; Bogdan e Biklen,1994). To data collecting, we used the text production notebooks to verify the proposals and the texts produced, and we realized the semi-structured interviews with the students to know what they think and say about the text production in school. The text production proposals were grouped according to their similar characteristics and organized in five categories: title, theme, scenes, story continuing, and, lastly, problem-situation and image. These proposals were artificial, and on them, the text was seen as a product to certify linguistic knowledges. When we analyzed the students’ texts, we noticed the presence of discursive elements that had the intention of activating the interest of the interlocutor and we tried to know what the students had to say about the writing process. In the interviews realized with the learners, we verified they understood the writing as a scholar chore. Furthermore, they acknowledge their classmates and the teacher as their interlocutors and that’s why they used different thematic and intertextual resources to stimulate interest, cause impact and produce empathy. Therefore, they were conscientious about the practice of writing and reading, and they knew what classmates and teachers thought of their produced texts. These interaction moments occurred in text production classes caused the anticipation of expected behaviors by the subjects involved in the production and reception of the texts.